Anguilla rostrata - Angulo, Arturo; Betts, Joel T.; González-Alemán, Néstor J.; Castañeda, Edgar; Berghe, Eric Van Den; Elías, Diego J.; Mcmahan, Caleb D.; Matamoros, Wilfredo A. (Zenodo, 2023)
Anguilla rostrata (Lesueur 1817) (Fig. 6G). American Eel; Anguila, Anguila de Mar, Anguila Verdadera, Anguila Americana Vouchers: UCR 0448-006 (1) and 0457-015 (1). Distribution: Western Atlantic Ocean; from southern Greenland to northwestern Venezuela; entering estuaries and littoral lagoons and ascending river courses; (Nicaragua) Co, UI, WK, Pr, GM, KP, Es, BF and IM (Atlantic); 0–350 masl; Per, Dia, Cat. Occurrence and conservation status: Nat; EN A2bd (2017), population trend decreasing. Literature: Villa (1982: 81; detailed description, including illustrations and an identification key, and information on distribution and ecology), Bussing (1998: 64; brief description, including illustrations and an identification key, and information on distribution, with a map, and ecology), Gros & Miguel-Frithz (2010: 175; brief description, including illustrations, and information on distribution and ecology, plus indigenous science and ethnoichthyology), Robertson & Van Tassell (2019: 2770; detailed description, including illustrations, and information on distribution, with a map, and ecology) and Angulo (2021: 21; listed, including information on distribution). Published as part of Angulo, Arturo, Betts, Joel T., González-Alemán, Néstor J., Castañeda, Edgar, Berghe, Eric Van Den, Elías, Diego J., Mcmahan, Caleb D. & Matamoros, Wilfredo A., 2023, Continental fishes of Nicaragua: diversity, distribution and conservation status; with an annotated and illustrated checklist of species and an identification guide to families, pp. 1-89 in Zootaxa 5376 (1) on page 16, DOI:10.11646/zootaxa.5376.1.1, http://zenodo.org/record/10208788